Post a New Question

math

posted by .

I've to solve 3x^2 + 6x +3 =0 by factoring. Thus, after solving I got the answer as 3(x + 1)^2.

Please correct me if I'm wrong.

  • math -

    3x^2 + 6x +3 =0
    first divide each term by 3, the fact that the right side is zero and zero divided by anything is zero, we can just drop the 3
    x^2 + 2x + 1 = 0
    (x+1)^2 =
    take √ of both sides
    x+1 = 0
    x = -1

    You had it factored correctly, but you "lost " your equation by dropping the =0 part.

  • math -

    Oh, thanks a lot!

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question